Caregiver Knowledge and Anti-Tuberculosis Treatment Adherence in Pediatric Patients: A Cross-Sectional Analytic Study at a District Referral Hospital - Dedi Kurniawan; Yuana Wijayanti; Galuh Kumalasari; Jok Thikuiy Gang (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2026)
Pediatric tuberculosis (TB) remains a major public health challenge in high-burden settings, where treatment success largely depends on consistent caregiver-mediated adherence to anti-tuberculosis therapy (OAT). However, evidence regarding the relationship between caregiver knowledge and OAT adherence among pediatric TB patients in Indonesian district hospital settings remains limited. This study aimed to examine the association between caregiver knowledge of TB and OAT with treatment adherence among pediatric TB patients attending the outpatient clinic of RSUD Kanjuruhan. A cross-sectional analytic study was conducted among 32 caregiver–patient dyads recruited through total sampling. Caregiver knowledge was assessed using a validated structured questionnaire, while adherence was measured using the eight-item Morisky Medication Adherence Scale (MMAS-8). Bivariate analysis employed Spearman’s rank correlation, followed by multivariate logistic regression to identify independent predictors of adherence. Most caregivers demonstrated good knowledge levels (62.5%), and 84.4% of pediatric patients were classified as adherent. Spearman’s analysis showed a strong positive correlation between caregiver knowledge and OAT adherence (r = 0.745; p < 0.001). After adjustment for confounders, good caregiver knowledge remained the strongest independent predictor of adherence (aOR = 6.84; 95% CI: 2.11–22.17; p < 0.001), alongside secondary-level education or above (aOR = 3.12; 95% CI: 1.02–9.55; p = 0.046). These findings highlight the importance of integrating structured, education-tailored caregiver education into routine pediatric TB care to improve treatment adherence and completion rates.